Laparoscopic Cholecystectomy (LC): Toward Zero Error [Retracted] - Coco, Danilo; Leanza , Silvana (Open Access Macedonian Journal of Medical Sciences, 2020)
In 1990, laparoscopic cholecystectomy (LC) was considered the new beginning of an exciting period in the management of pathologies associated with gallbladder. Two decades later, biliary morbidity alongside LC is nearly thrice higher compared to conventional open surgery. In the 1990s, Strasberg et al. explained the manner, in which a critical view of safety can be attained and the manner in which vascular injuries and accidental biliary caused by unclear anatomy, incautious control of bleeding, or rare variations could be prevented. The aforementioned principles have been overlooked until recently, only gaining recognition in the past 15 years. This review seeks to explore the aspect of safety in LC based on various techniques.